Surface coatings select their micro and macrofouling communities differently on steel. (November 2019) - Agostini, Vanessa Ochi; Macedo, Alexandre José; Muxagata, Erik; Pinho, Grasiela Lopes Leães
Abstract: Previous studies have shown the effect of surface coatings on biofouling; however, they did not take into account the interaction of the micro and macrofouling communities, the effect of substrate orientation and the zooplankton-zoobenthic coupling together. Therefore, the aim of this study was to evaluate the effect of Zn- and Cu2 O-based coatings on micro and macrofouling on steel surfaces, while also observing the role of substrate orientation and zooplankton supply. An experiment was carried out in the Patos Lagoon Estuary in southern Brazil for three months between spring and summer, where ASTM-36 steel plates represented different coatings (Zn- and/or Cu2 O-based) and orientations (vertical and horizontal). To assess the zooplankton supply, sampling was carried out weekly using a 200 μm plankton net. Zn-based coating positively affected microfouling density compared to uncoated surfaces. The same pattern was observed with macrofouling, associated with vagile fauna preference, which represented 70% of the settled macrofoulers. Cu2 O-based antifouling painted surfaces showed the highest microfouling density inhibition, while Zn + Cu2 O-based coating did not affect the bacteria adhesion but showed lower density compared to Zn-based coating alone. The coatings combination showed the highest invertebrate inhibition. In this way, the macrofouling community was more sensitive than microfouling was to the antifouling coatings tested. The substrate orientation only affected macrofouling, horizontal surfaces being more attractive than vertical. Meroplankton, tychoplankton and holoplankton were recorded on the surfaces, although their representation in plankton was not proportional to the recruits recorded on the substrates. This was probably due to fast dispersion, the interactions of other factors and/or ecological succession stage. Surface coating, substrate orientation, and zooplankton supply interacted with the biofouling process on steel in different ways depending on the organism evaluated. Therefore, copper oxide- and zinc-based coatings were not suitable as coatings to avoid the total biofouling establishment. Graphical abstract: Image 1 Highlights: Biofouling represents a problem for naval engineering. Chemical coatings are applied on surfaces to avoid the establishment of organisms. Zn and Cu2 O-based coatings affect micro and macrofouling in different ways. Macrofouling is more sensitive to antifouling coatings than microfouling is. Zn and Cu2 O-based coatings were not suitable to avoid total biofouling on steel. Abstract : Main finding of the work: Zn and Cu2 O-based coatings are not suitable to avoid the total biofouling establishment. Macrofouling is more sensitive than microfouling to these coatings.